Management of Open Apex Using Alternative Techniques: Series of 3 Case Reports - Satabdi Pattanaik1, Satyajit Mohapatra2, Naomi Ranjan Singh1, K. Swapna Kumari3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Traumatic injuries during early childhood interfere with root development leading to the formation of atooth with an open apex. Apexification is considered as the best choice for the treatment of such cases. UseMineral Trioxide Aggregate (MTA) as apical plug material optimizes the treatment outcome. Other thanMTA different techniques are also used to restore the function and stability of the immature permanenttooth. In this case report 3 different techniques are used to treat the open apex. In the first case, MTA apicalplug along with backfill was done. Complete canal obturation with MTA and custom cone technique wereperformed for the second and third cases respectively.